N-Terminal pro-Brain Natriuretic Peptide and Associations With Brain Magnetic Resonance Imaging (MRI) Features in Middle Age: The CARDIA Brain MRI Study - Ferguson, Ian T.; Elbejjani, Martine; Sabayan, Behnam; Jacobs, David R.; Meirelles, Osorio; Sanchez, Otto A.; Tracy, Russell; Bryan, Nick; Launer, Lenore J. (Frontiers in Neurology, 2018)
Objective As a part of research on the heart-brain axis, we investigated the association of N-terminal pro-Brain Natriuretic Peptide (NT-proBNP) with brain structure and function in a community-based cohort of middle-aged adults from the Brain MRI sub-study of the Coronary Artery Risk Development in Young Adults (CARDIA) Study. Approach and Results In a cohort of 634 community-dwelling adults with a mean (range) age of 50.4 (46-52) years, we examined the cross-sectional association of NT-proBNP to total, gray (GM), and white matter (WM) volumes, abnormal WM load, and WM integrity, and to cognitive function tests (The Digit Symbol Substitution Test (DSST), the Stroop test, and the Rey Auditory-Verbal Learning Test (RAVLT)). These associations were examined using linear regression models adjusted for demographic and cardiovascular risk factors and cardiac output. Higher NT-proBNP concentration was significantly associated with smaller GM volume (beta= -3.44; 95% CI= -5.32, -0.53; p=0.003), even after additionally adjusting for cardiac output (beta= -2.93; 95% CI= -5.32,-0.53; p<0.02). Higher NT-proBNP levels were also associated with lower DSST scores. NT-proBNP was not related to WM volume, WM integrity, or abnormal WM load. Conclusions In this middle-aged cohort, sub-clinical levels of NT-proBNP were related to brain function and specifically to GM and not WM measures, similar to findings in older cohorts. Further research is warranted into biomarkers of cardiac dysfunction as a target for early markers of a brain at risk.